2006
DOI: 10.1007/s00231-006-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Exact analytical solutions for thermosolutal Marangoni convection in the presence of heat and mass generation or consumption

Abstract: The steady laminar thermosolutal Marangoni convection in the presence of temperature-dependent volumetric heat sources/sinks as well as of a firstorder chemical reaction is considered in this paper. Assuming that the surface tension varies linearly with temperature and concentration and that the interface temperature and concentration are quadratic functions of the interface arc length x, exact analytical similarity solutions are obtained for the velocity, temperature and concentration fields. The features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
(19 reference statements)
0
42
0
Order By: Relevance
“…14,15,20 Further, the surface also was assumed to vary linearly with the concentration and the thermosolutal surface tension radio parameter was introduced to describe the mass transfer. [21][22][23][24][25] Zheng et al 20 established the Marangoni convection over a liquid-vapor surface due to an imposed temperature gradient by the Adomian analytical decomposition technique and the Páde approximant technique. Chamkha and coworkers [21][22][23] considered the steady laminar MHD thermosolutal Marangoni convection in the presence of a uniform applied magnetic field in the boundary layer approximation.…”
Section: Mcconaghy and Finlaysonmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15,20 Further, the surface also was assumed to vary linearly with the concentration and the thermosolutal surface tension radio parameter was introduced to describe the mass transfer. [21][22][23][24][25] Zheng et al 20 established the Marangoni convection over a liquid-vapor surface due to an imposed temperature gradient by the Adomian analytical decomposition technique and the Páde approximant technique. Chamkha and coworkers [21][22][23] considered the steady laminar MHD thermosolutal Marangoni convection in the presence of a uniform applied magnetic field in the boundary layer approximation.…”
Section: Mcconaghy and Finlaysonmentioning
confidence: 99%
“…[21][22][23][24][25] Zheng et al 20 established the Marangoni convection over a liquid-vapor surface due to an imposed temperature gradient by the Adomian analytical decomposition technique and the Páde approximant technique. Chamkha and coworkers [21][22][23] considered the steady laminar MHD thermosolutal Marangoni convection in the presence of a uniform applied magnetic field in the boundary layer approximation. And exact analytical solutions for the velocity, temperature and concentration boundary layers were reported.…”
Section: Mcconaghy and Finlaysonmentioning
confidence: 99%
See 2 more Smart Citations
“…It has received much attention in recent years [2]. In the mid 1860s, Marangoni found the phenomenon that the natural convection dominated by liquid gravity gradually disappeared in a microgravity environment, whereas, at the interface of liquid, the surface tension plays a leading role and causes a surface tension gradient [3]. In 1978, Napolitano observed that there may be a dissipative layer in liquid-liquid or liquid-gas system, which is called Marangoni boundary layer [4].…”
Section: Introductionmentioning
confidence: 99%